2004
DOI: 10.1257/0022051043004577
|View full text |Cite
|
Sign up to set email alerts
|

Field Experiments

Abstract: Experimental economists are leaving the reservation. They are recruiting subjects in the field rather than in the classroom, using field goods rather than induced valuations, and using field context rather than abstract terminology in instructions. We argue that there is something methodologically fundamental behind this trend. Field experiments differ from laboratory experiments in many ways. Although it is tempting to view field experiments as simply less controlled variants of laboratory experiments, we arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
1,500
0
38

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,237 publications
(1,553 citation statements)
references
References 110 publications
15
1,500
0
38
Order By: Relevance
“…Our experimental design stems from our intention to mimic the field as well as possible: we provided our subjects with a real resource problem description under approximation of an indefinite time horizon and allowed for face-to-face communication, as it has been observed that communities dealing with CPRs keep up frequent face-to-face communication (Pretty 2003). In these respects, one can classify our experiment as a "framed laboratory experiment" (see Harrison and List 2004 for a classification of experiments).…”
Section: Experimental Designmentioning
confidence: 99%
“…Our experimental design stems from our intention to mimic the field as well as possible: we provided our subjects with a real resource problem description under approximation of an indefinite time horizon and allowed for face-to-face communication, as it has been observed that communities dealing with CPRs keep up frequent face-to-face communication (Pretty 2003). In these respects, one can classify our experiment as a "framed laboratory experiment" (see Harrison and List 2004 for a classification of experiments).…”
Section: Experimental Designmentioning
confidence: 99%
“…To address such shortcoming, there have been attempts to complement knowledge gained from controlled laboratory studies, through experimental field work providing higher external validity (G. W. Harrison & List, 2004;Proestakis et al, 2013). However, those who have explored the relationship between alcohol and risky behaviour in real drinking environments have revealed varied findings (e.g., Hopthrow et al, 2014;Lyvers et al, 2011;Lyvers et al, 2015;Proestakis et al, 2013), which at times show inconsistencies with laboratory based work (Burian et al, 2002;Lane et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The experiment is implemented as an "artefactual field experiment" (Harrison and List 2004) by running our experiment and survey over the internet rather than in face-to-face interaction (as is the case, for example, in the World Values Survey, Glaeser et al 2000or Fehr et al 2003. Using the internet allows participants to make choices and give responses in their habitual environment (e.g.…”
mentioning
confidence: 99%